2009
DOI: 10.1590/s0103-166x2009000400007
|View full text |Cite
|
Sign up to set email alerts
|

Estudo dos transtornos cognitivos decorrentes da infecção pelo HIV-1

Abstract: A infecção pelo vírus da imunodeficiência humana atinge o Sistema Nervoso Central nos estágios iniciais, causando manifestações neuropsicológicas. Com o objetivo de estudar o desempenho de indivíduos infectados por este vírus em relação às funções cognitivas, foram avaliados 20 pacientes com contagem de linfócitos CD4+ acima de 200 células/mm³, utilizando-se a Escala de Inteligência Wechsler para Adultos. Destes, cinco (25%) eram do sexo masculino e 15 (75%) do sexo feminino, com média de idade de 39,65 desvio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
2
0
5
Order By: Relevance
“…The worst cognitive scores were perceived in information processing speed, visual memory, attentional alternation, and visual perception. Deficits related to memory, attention, processing speed, and problem-solving ability are the most frequently observed in HIV+ people (Kalil et al, 2009;Cattie et al, 2012;DeVaughn et al, 2015;Nascimento et al, 2015;Antwerpes et al, 2020). Távora et al (2016) indicate that such deficits are usually identified later in HIV+ elderly, as they take longer to get the diagnosis and start follow-up, which can worsen the impact of these problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The worst cognitive scores were perceived in information processing speed, visual memory, attentional alternation, and visual perception. Deficits related to memory, attention, processing speed, and problem-solving ability are the most frequently observed in HIV+ people (Kalil et al, 2009;Cattie et al, 2012;DeVaughn et al, 2015;Nascimento et al, 2015;Antwerpes et al, 2020). Távora et al (2016) indicate that such deficits are usually identified later in HIV+ elderly, as they take longer to get the diagnosis and start follow-up, which can worsen the impact of these problems.…”
Section: Discussionmentioning
confidence: 99%
“…The first studies on cognitive deficits and emotional symptoms in HIV+ Brazilian elderly began in the 2000s, but are still scarce ( Kalil et al, 2009 ; Christo, 2010 ; Nascimento et al, 2015 ; Pinheiro, 2016 ; Oliveira et al, 2017 ). Considering this context, the purpose of this study was to identify factors associated with HAND and symptoms of anxiety and depression in HIV+ Brazilian elderly people on ART.…”
Section: Introductionmentioning
confidence: 99%
“…Assim como o HIV-2, o HIV-1 também apresenta como alvo principal os linfócitos CD4+, no entanto outras células também são acometidas por esse vírus, como a linhagem monócito-macrófago (Holt et al, 2012). O mecanismo invasivo do vírus HIV se deve a algumas características que as células infectadas por ele possuem em comum, a exemplo dos receptores na membrana celular, como o CXCR4 e o CCR5 (Kalil et al, 2009).…”
Section: Hiv E Infecção Do Sistema Nervoso Centralunclassified
“…As funções cognitivas consistem em um conjunto de habilidades (percepção, linguagem, memória, atenção que não podem ser observadas diretamente, mas que é possível inferir pelo comportamento (Kalil et al, 2009). A infecção do SNC pelo vírus HIV pode acometer áreas especiais relacionadas com a cognição, desencadeando assim declínio cognitivo e até mesmo demência.…”
Section: áReas Do Snc Afetadas Pelo Hivunclassified
“…(31) . Em um estudo no Rio de Janeiro foram avaliados 20 indivíduos e apenas um apresentou desempenho das funções cognitivas muito abaixo da média (33) .…”
Section: B Hiv E Alterações Neurocognitivasunclassified